Marking Black. - Ingberman, Jeanette; Burnside, Madeleine (New York : Bronx Museum of the Arts, 1980)
Bell, Larry ; Colo ; Ewing, Lauren ; Gitlin, Michael ; Gobhai, Mehlli ; Hafif, Marcia ; Kupferman, Moshe ; Neustein, Joshua ; Scully, Sean ; Serra, Richard ; Tevet, Nahum ; Timmons, Randall ; Walkingstick, Kay ; Willenbecher, John
Marking Black, Bronx Museum of the Arts, Bronx, New York, January 24 - March 9, 1980
boek